Stabilizing Pre-Run-Time Schedules With the Help of Grace Time - Magalhães, Antonio Pessoa (1999)
This paper discusses the stability of a feasible pre-run-time schedule for a transient overload introduced by processes re-execution during an error recovery action. It shows that the stability of a schedule strictly tuned to meet hard deadlines is very small, invalidating thus backward error recovery. However, the stability of the schedule always increases when a real-time process is considered as having a nominal and a hard deadline separated by a non-zero grace time. This is true for sets of processes having arbitrary precedence and exclusion constraints, and executed on a single or multiprocessor based architecture. Grace time is not just the key element for the realistic estimation of the timing constraints of real-time error processing techniques. It also allows backward error recovery to be included in very efficient pre-run-time scheduled systems when the conditions stated in this paper are satisfied. This is a very important conclusion, as it shows that fault-tolerant hard real-time systems do not have to be extremely expensive and complex.